The Role of Digestive Disorders in Melasma - Marjan Mahjour; Mohammad Reza Noras; Arash Khoushabi; Roshanak Salari (Tehran University of Medical Sciences, 2018)
Melasma is a skin disorder characterizing by hyperpigmentation affecting the sun-exposed areas. This disorder, accounts for 0.25 to 4% of the patients observed in skin clinics in south East Asia. In spite of several reports according to the relationship between digestive problems such as gastritis with melasma, these disorders are not included in the diagnostic criteria of melasma in the texts. This study aims to find the relationship between digestive problems and melasma. In this study, the relationship between gastric problems and melasma was investigated by searching the Persian medicine references such as the Canon of Medicine by Avicenna and Al-Havi of Razi with the terms such as stomach, melasma (kalaf in the Canon) and also the electronic databases such as PubMed, Scopus, Magiran with the keywords of gastritis, stomach, melasma, hyperpigmentation and digestive problems. This study searched the etiology and symptoms of melasma. The results showed accompaniment between some digestive disorders and melasma in Al-Havi and the Canon as well as in articles retrieved from the electronic databases. However, we noticed poor attention to the relationship between digestive problems and melasma due to attention to various topical creams produced by different companies. Considering the results, it is required to pay attention to systemic aspects such as digestive problems in the treatment of melasma. The researchers suggest doing more studies about these issues to find this relationship to be included in one of the main diagnostic criteria of melasma.